The British Library's Approach to AACR2 - Lynne Brindley (Information Technology and Libraries, 1981)
The formal commitment of the British Library to AACR2 and Dewey 19 entailed substantial changes to the U.K. MARC format, the BLAISE Filing Rules, and a variety of products produced for the British Library itself and for other libraries, including the British National Bibliography. The British Library file conversion involved not only headings but also algorithmic conversion of the descriptive cataloguing.